From Prose to Picture: Critical Reflections on the Road and the Journey in John Steinbeck’s and John Ford’s The Grapes of Wrath - Festa, Beatrice Melodia (Literatūra, 2025)
Since its release in 1940, John Ford’s adaptation of John Steinbeck’s The Grapes of Wrath has sustained significant popular interest. However, the film adaptation has been more frequently analyzed for its thematic content than appreciated for its visual aesthetics, likely due to its connection with Ford’s established cinematic legacy and its alignment with the broader corpus of works addressing the socio-economic struggles of Depression-era America. The aim of this article is to critically examine the visual significance of the road and the archetypal myth of the highway in Ford’s interpretation of The Grapes of Wrath. The analysis begins by exploring the theme of the journey as represented in Steinbeck’s novel, and then narrowing the focus to the portrayal of this motif in Ford’s cinematic adaptation. Within the literary text, the journey serves as a metaphor for dispossession, whereas in the film, the motifs of the “road” and “travel” substantiate the film’s alignment with the road movie genre. Ultimately, this article argues that Steinbeck’s novel was instrumental in shaping Hollywood’s enduring fascination with the journey and the road, themes which would later be re-elaborated in the road movie, a cinematic reworking of the road narrative.